Multifunctional composite flexible fabric and preparation method thereof
Through electrostatic spinning process, the composite flexible fabric with multi-layer structure is formed, combining radiation refrigeration, energy harvesting, hydrophobic and antibacterial functions, and solves the challenges of flexible smart fabrics in thermal comfort, energy supply and surface cleaning, achieving high efficiency and multi-purpose Overall solution to functionality.
Patent Information
- Application Number
- CN202411343859.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Flexible smart fabrics have challenges in thermal comfort, continuous energy supply and surface cleaning, and the prior art is difficult to achieve a simplified and multifunctional overall solution.
The electrospinning process is used to form a composite flexible fabric composed of a polymer electrospinned fiber layer and a nanofunctional electrospinned fiber layer, combining radiation refrigeration, energy harvesting, hydrophobic and antibacterial functions.
Passive daytime radiation refrigeration is realized, providing continuous heat dissipation and cooling with zero energy consumption, with efficient energy harvesting capabilities, good hydrophobicity and broad-spectrum antibacterial activity, and improving the overall performance of the fabric.
Smart Images

Figure CN119433828A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible wearable devices, and in particular to a multifunctional composite flexible fabric and a preparation method thereof. Background Art
[0002] With the advancement of science and technology, production and the market have higher and higher expectations for flexible wearable devices. Such devices usually include functional devices such as displays, sensors, batteries, etc., which can work for a long time on the surface of the human body or in the human body. Thanks to their light, soft and skin-friendly characteristics, flexible wearable electronic devices, especially flexible fabrics, have shown great potential and application value in the fields of human health monitoring, sports tracking, medical diagnosis, etc.
[0003] Ensuring that users get the best thermal comfort is an important functional indicator of flexible fabrics. Especially when the wearer is exposed to direct sunlight during long-term outdoor activities, it is more likely to cause heat stress disorder and overheating of electronic devices. At this time, how to make flexible fabrics provide users with better thermal comfort is particularly critical. Therefore, finding a simple and effective cooling technology integrated into flexible fabrics is a technical problem facing the current fabric field. Radiative cooling is a passive cooling technology. Unlike traditional cooling technology, which is active cooling and requires external energy such as electricity and fuel input, radiative cooling is a cooling technology that uses the object's own characteristics or environmental conditions without external energy input to achieve a cooling effect. Compared with traditional air-conditioning systems that require high energy consumption, passive radiative cooling systems can radiate heat to the cold external universe through the atmospheric window (8-13μm) with almost no energy consumption. Therefore, passive radiative cooling technology has gradually attracted people's attention in recent years, but currently this technology is mainly used in outdoor buildings, thermoelectric equipment and dew collection.
[0004] In addition, achieving a continuous and stable long-term power supply is also an important issue for flexible smart fabrics. Traditional power sources (such as batteries and supercapacitors) have short lifespans, poor rigidity, and are difficult to integrate with fabrics. Therefore, harvesting energy from the environment is an important direction for simplifying processes and improving sustainability. Triboelectric nanogenerators (TENGs) can harvest waste mechanical energy from human movement and power electronic devices, which has advantages in smart fabric design. This is a promising solution that can reduce the thermal load and energy load in smart fabric design and greatly simplify the thermal management and energy supply systems in smart fabrics.
[0005] To solve the problem of surface contamination of flexible smart fabrics, the research focuses on enhancing the surface hydrophobicity and antibacterial properties. The introduction of hydrophobicity is conducive to the formation of a thin air layer on the fabric surface, which effectively prevents the rapid absorption of liquids and improves the anti-adhesion to bacterial solutions. When water rolls off the fabric, it takes away the residual dust particles, thus achieving a significant self-cleaning effect. In addition, given the evolution and development of new viruses and the potential catastrophic consequences for human well-being, preventive measures must be taken to address this major safety risk. Bacterial growth easily poses a major threat to the sustainable application of flexible fabrics and the health of the wearer. Therefore, it is very important to achieve the unity of hydrophobicity and antibacterial properties in flexible fabrics.
[0006] At present, the above-mentioned multiple functional indicators required by flexible fabrics are usually achieved through surface integration or superposition of different functional modules. On the one hand, the fabric structure formed by the stacking integration method is complex and the integration process is difficult. On the other hand, this complex stacking structure will also increase the thermal load and electrical load of the flexible fabric, which will not only affect the comfort of the wearer, but also put forward higher requirements for continuous power supply. At the same time, the use of this stacked microstructure will enhance the irregularity of the surface, increase the possibility of surface contamination and bacterial reproduction, and have a negative impact on the durability and long-term stability of the fabric. Therefore, how to reasonably design and comprehensively optimize, solve problems such as thermal comfort, continuous energy supply and surface cleaning, and provide a convenient overall solution for smart flexible fabrics is an important topic in the field of smart fabrics. Summary of the invention
[0007] Based on the above-mentioned problems of the prior art, the present invention aims to explore an overall solution for flexible fabrics, that is, to provide a composite flexible fabric with a simple structure and multiple functions, which can simultaneously meet the requirements of flexible fabrics for thermal comfort, continuous and stable energy supply, and hydrophobic and antibacterial functions, and provide a multifunctional integration method of the flexible fabric, that is, a preparation method of the multifunctional flexible fabric, so as to solve the technical problems such as the current complex structure and integration difficulty of the above-mentioned intelligent flexible fabrics.
[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical scheme.
[0009] The present invention first provides a multifunctional composite flexible fabric, which has multiple functions of radiation cooling, energy collection, hydrophobicity and antibacterial. The composite flexible fabric is composed of several layers of electrospun fiber layers, each layer is formed by electrospinning in an upper and lower order; it includes at least two layers of polymer electrospun fiber layers and at least one layer of nano-functional electrospun fiber layer, wherein the nano-functional electrospun fiber layer is an intermediate layer, and forms a sandwich structure with the polymer electrospun fiber layers located on the upper and lower surfaces respectively.
[0010] The polymer electrospun fiber layer is formed by a plurality of polymer fibers crossing to form a three-dimensional mesh porous structure (for the convenience of distinction, the plurality of polymer fibers constituting the polymer electrospun fiber layer are recorded as the first polymer fibers); the nano-functional electrospun fiber layer comprises a plurality of polymer fibers and a plurality of nanoparticles, wherein the polymer fibers cross to form a three-dimensional mesh porous structure, and the nanoparticles are uniformly distributed in or on the mesh porous structure formed by the polymer fibers (for the convenience of distinction, the plurality of polymer fibers contained in the nano-functional electrospun fiber layer are recorded as the second polymer fibers). The material of the polymer fiber is one or more selected from polyvinylidene fluoride (PVDF) and its series of copolymers, preferably one or more of PVDF, polyvinylidene fluoride-hexafluoropropylene PVDF-HFP, polyvinylidene fluoride-trifluoroethylene PVDF-TRFE. The nanoparticles are at least one of SiO2 / ZnO core-shell particles, SiO2 / Zn2SiO4 core-shell particles or SiO2 / ZnO / ZIF-8 core-shell particles.
[0011] Furthermore, the composite flexible fabric is composed of three single-layer electrospun layers, which are, in order from top to bottom, a single-layer first polymer electrospun fiber layer, a nano-functional electrospun fiber layer, and a second polymer electrospun fiber layer.
[0012] Furthermore, the diameter of the polymer fibers of the polymer electrospun fiber layer, namely the first polymer fibers, is 100 to 700 nm; and the diameter of the polymer fibers of the nano-functional electrospun fiber layer, namely the second polymer fibers, is 200 to 1000 nm.
[0013] Furthermore, the particle size of the nanoparticles is 500-900 nm, and the content of the nanoparticles is 40-60% of the mass fraction of the polymer fibers (second polymer fibers) in the nano-functional electrospun fiber layer.
[0014] Further, the SiO2 / ZnO core-shell particles are formed by the core-shell structure of fine nano ZnO particles wrapped on the surface of SiO2 nanospheres. Further, the SiO2 / Zn2SiO4 core-shell particles are formed by the surface solid phase reaction of SiO2 nanospheres and nano ZnO particles on the surface. Further, the SiO2 / ZnO / ZIF-8 core-shell particles are formed by in-situ chemical assembly of SiO2 nanospheres, nano ZnO particles and bulk nano ZIF-8 particles. The nano ZnO particles are uniformly dispersed on the surface of the SiO2 nanospheres, and the bulk ZIF-8 particles are further wrapped on the surface to form.
[0015] Furthermore, the diameter of the SiO2 nanospheres is 500-600 nm, the diameter of the nano ZnO particles is 10-30 nm, and the size of the bulk nano ZIF-8 particles is 90-110 nm.
[0016] In the design of the composite flexible fabric of the present invention to achieve the best thermal comfort, the inventor adopted a method of controlling thermal comfort by designing the fabric structure and material selection of passive radiation cooling. The inventor's idea is based on the fact that when radiation heat dissipation accounts for 40-60% of the total heat dissipation of the human body, passive radiation cooling fabrics can show significant advantages in personal thermal management. The above-mentioned composite flexible fabric provided by the present invention is formed by stacking a polymer fiber layer and a polymer fiber layer modified by core-shell nanoparticles. The three-dimensional mesh porous structure formed by the stacking can strongly scatter the incident sunlight to obtain a strong solar reflectivity. For example, in Example 1 of the present invention, the solar reflectivity of the composite flexible fabric reaches 84.7%; in addition, the rich chemical bonds (such as Si-O bonds, CF bonds, etc.) contained in the composite structure composed of the flexible fabric fiber layer and the core-shell nanoparticles of the present invention can strongly emit infrared radiation in the range of 8-13μm to obtain a strong infrared emissivity. For example, in Example 1 of the present invention, the infrared emissivity of the composite flexible fabric reaches 94.9%. Combining these two aspects enables the flexible fabric to achieve passive daytime radiation cooling, and can provide continuous heat dissipation and cooling with zero energy consumption for the flexible fabric all day long.
[0017] The main component of the composite flexible fabric of the present invention is polymer electrospun fibers, in which the polymer PVDF and its series of copolymers are ferroelectric polymers, and their β phase has high electron affinity, large spontaneous polarization and excellent polarization stability, and is an excellent friction nanogenerator (TENGs) material. At the same time, the present invention adopts an electrostatic spinning process to form each fiber layer of the composite flexible fabric. The strong voltage added to the polymer during the electrostatic spinning process will induce the polymer to transform from a non-polar α phase to a polar β phase, thereby enhancing the piezoelectric properties of the fabric and improving the efficiency of mechanical energy collection. In this regard, it is equivalent to assembling a number of friction nanogenerators in the composite flexible fabric of the present invention, so that the composite flexible fabric can rely on the charging pump effect of the friction point potential to effectively convert the tiny mechanical energy discarded in the environment into electrical energy, thereby achieving the purpose of energy collection. For example, the flexible fabric prepared in Example 1 of the present invention, when the external load is 60MΩ, the maximum output power of the friction nanogenerator formed can reach 10.97mW·m -2 .
[0018] Hydrophobicity and antibacterial properties are very important for composite flexible fabrics, which help to reduce surface contamination and bacterial growth. The polymer PVDF and its series of copolymers in the composite flexible fabric of the present invention are fluorine-containing polymers, have low surface energy, and have good hydrophobicity. For example, the water contact angle of the composite flexible fabric obtained in Example 1 is 134.3°, which has good hydrophobicity. This hydrophobicity prevents the rapid absorption of water, allowing it to effectively carry away pollutants on the surface. On the other hand, the core-shell structured nanoparticles contained in the composite flexible fabric can produce a photocatalytic effect, by absorbing ultraviolet light in the environment, generating active oxygen species and then destroying the cell membrane of bacteria, thereby causing the death of bacteria. For example, the composite flexible fabric obtained in Example 1 has an antibacterial rate of 99.9% against Staphylococcus aureus and Escherichia coli in the co-culture experiment, showing efficient broad-spectrum antibacterial activity.
[0019] In addition, the present invention also provides a method for preparing the above-mentioned multifunctional composite flexible fabric, comprising the steps of: (1) dissolving a polymer material in a mixed solvent to form a precursor solution; (2) adding a functional nanoparticle material to the precursor solution to obtain a composite solution; (3) sequentially performing continuous electrospinning on the precursor solution, the composite solution and the precursor solution, and obtaining the multifunctional composite flexible fabric after drying.
[0020] Furthermore, the polymer material in step (1) is selected from polyvinylidene fluoride PVDF, polyvinylidene fluoride-hexafluoropropylene PVDF-HFP and polyvinylidene fluoride-trifluoroethylene PVDF-TRFE. The mixed solvent contains a high boiling point solvent and a low boiling point solvent; the high boiling point solvent is one of N,N-dimethylformamide DMF or N,N-dimethylacetamide DMAC; the low boiling point solvent is acetone; the volume ratio of the high boiling point solvent to the low boiling point solvent is 6:4 to 4:6. The mass fraction of the polymer material in the precursor solution is 13 to 16 wt%.
[0021] Furthermore, the functional nanoparticle material in step (2) is selected from SiO2 / ZnO core-shell particles, SiO2 / Zn2SiO4 core-shell particles and SiO2 / ZnO / ZIF-8 core-shell particles. The functional nanoparticle material accounts for 40-60% of the mass fraction of the polymer material in the composite solution.
[0022] Furthermore, in the electrospinning process described in step (3), the spinning voltage is 8 to 12 kV, the propulsion speed is 0.8 to 1.0 mL / h, and the receiving distance is 14 to 18 cm.
[0023] Furthermore, the specific preparation method of the functional nanoparticle material in step (2) is:
[0024] 1) adding SiO2 particles, an inorganic zinc source and ascorbic acid into an aqueous solution, and subjecting the aqueous solution to ultrasonic treatment to obtain a SiO2 dispersion; the inorganic zinc source is one of zinc acetate and zinc nitrate;
[0025] 2) adding hexamethylenetetramine HMTA to the SiO2 dispersion, stirring and then ultrasonically treating to obtain a first pre-solution; the molar ratio of SiO2: inorganic zinc source: ascorbic acid: hexamethylenetetramine is 8:10:3:20.
[0026] 3) subjecting the first pre-solution to a solution reaction at a temperature of 90 to 100° C. for 2 to 4 hours to obtain a precipitated product;
[0027] 4) centrifuging the precipitated product, washing and drying it to obtain a powder;
[0028] 5) grinding the powder and calcining in an air atmosphere at a heating rate of 5 to 10° C. / min and a holding time of 1 to 3 hours to obtain the SiO2 / ZnO core-shell particles at a temperature of 600 to 800° C. and the SiO2 / Zn2SiO4 core-shell particles at a temperature of 900 to 1100° C.;
[0029] 6) mixing the SiO2 / ZnO core-shell particles, N,N-dimethylformamide (DMF) and 2-methylimidazole, and dispersing them by ultrasonic treatment to obtain a second pre-solution;
[0030] 7) The second pre-solution is subjected to a solution reaction, and the 2-methylimidazole and ZnO in the solution are dissolved by solvent heat to generate Zn 2+ Ion assembly, ZnO part is transformed into metal organic framework ZIF-8, and SiO2 / ZnO / ZIF-8 core-shell nanomaterials are obtained. The reaction temperature of the process is 90-110°C, and the reaction time is 1-3h. After the reaction, the precipitation product of SiO2 / ZnO / ZIF-8 core-shell nanomaterials is obtained.
[0031] 8) The precipitated product is centrifuged, washed, and dried to obtain the SiO2 / ZnO / ZIF-8 core-shell particles.
[0032] The beneficial results of the present invention are:
[0033] (1) The present invention selects a suitable process for structural design based on the multifunctional integration requirements of flexible fabrics. Electrospinning can rely on electrostatic force to form nanofiber membranes and achieve rich fiber structures. By adding different nanoparticles to the fibers, flexible fabrics with specific functions can be actively designed for different applications. The method of the present invention provides an optimized multifunctional fabric design strategy that uses a simple process to simultaneously integrate personal thermal management, energy collection, and hydrophobic antibacterial properties. The three functional requirements are comprehensively considered, and the structure is designed as a whole to achieve a synergistic effect rather than simply stacking functional units. It has reference significance for the design and preparation of flexible wearable devices. This simple multifunctional composite method can be expanded to other large-scale spinning processes, which is of great significance in the field of energy conservation and environmental protection.
[0034] (2) The composite flexible fabric prepared by the present invention adopts a bottom-up micro-nano structure design, relying on core-shell structure scattering particles and hierarchical porous fiber structure, nano scattering particles and nanofibers produce a synergistic effect, and the reflectivity in the entire solar spectrum range reaches 84.7%, and the infrared emissivity in the atmospheric window (8-13 μm) range reaches 94.9%. The temperature under sunny outdoor conditions is 2.9°C lower than that of commercial pure cotton fabrics.
[0035] (3) The composite flexible fabric prepared by the present invention integrates the energy harvesting function into the design of the radiant cooling fabric. The electrospinning process is used to form the fiber layers of the composite flexible fabric to obtain a fabric with piezoelectric properties. The composite flexible fabric can rely on the charging pump effect of the friction point potential to effectively convert the tiny mechanical energy wasted in the environment into electrical energy, thereby achieving continuous collection of waste mechanical energy and continuous power supply for flexible wearable devices.
[0036] (4) The composite flexible fabric prepared by the present invention has good hydrophobicity and antibacterial properties. When water flows over the fiber surface, it can effectively clean the dust remaining on the surface, achieving the purpose of self-cleaning. Since the added functional nanomaterial plays a photocatalytic antibacterial role, the fabric has a broad-spectrum and high-efficiency antibacterial ability. Its antibacterial rate against Staphylococcus aureus and Escherichia coli is both greater than 99.9%. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a scanning electron microscope (SEM) image of the SiO2 / ZnO / ZIF-8 core-shell nanoparticles prepared in Example 1.
[0038] Figure 2 This is a scanning electron microscope (SEM) image of the SiO2 / Zn2SiO4 core-shell nanoparticles prepared in Example 2.
[0039] Figure 3This is a scanning electron microscope (SEM) image of the SiO2 / ZnO core-shell nanoparticles prepared in Example 3.
[0040] Figure 4 Schematic diagram of the structure of the composite flexible fabric prepared in Example 1 and scanning electron microscope (SEM) images of each layer.
[0041] Figure 5 This is the UV-visible-near infrared band reflectivity curve and infrared emissivity curve of the composite flexible fabric prepared in Example 1.
[0042] Figure 6 This is a comparison chart of the cooling effects of the composite flexible fabric prepared in Example 1 and different materials in an outdoor environment on a sunny day.
[0043] Figure 7 The open circuit voltage characteristics of the friction nanogenerator assembled with the composite flexible fabric prepared in Example 1 as the friction material.
[0044] Figure 8 The external load and power characteristics of the friction nanogenerator assembled with the composite flexible fabric prepared in Example 1 as the friction material.
[0045] Fig. 9 The cyclic stability characteristics of the friction nanogenerator assembled with the composite flexible fabric prepared in Example 1 as the friction material.
[0046] Fig.10 This is a diagram of the surface water contact angle of the composite flexible fabric prepared in Example 1.
[0047] Fig.11 These are colony images of the composite flexible fabric prepared in Example 1 after co-culturing with Escherichia coli and Staphylococcus aureus. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention.
[0049] Example 1
[0050] Weigh 1.4142g P(VDF-HFP) and dissolve it in a mixed solvent of 5mL acetone and 5mL DMF, stir at 40℃ for 2h to obtain a polymer solution with a mass concentration of 14wt%, and prepare three polymer solutions in total; take 0.7071g SiO2 / ZnO / ZIF-8 core-shell nanoparticles (nanoparticles are 50% of the polymer mass) and add them to one of the polymer solutions, stir for 4h to obtain a composite solution; set the electrospinning machine parameters as spinning voltage of 10.5kV, propulsion rate of 0.8mL / h, and receiving distance of 15cm; successively transfer the polymer solution, composite solution, and polymer solution to the electrospinning machine for continuous electrospinning for 3h, 6h, and 3h, respectively; after spinning, transfer the composite fiber membrane to an oven and dry it at 60℃ for 8h to obtain a flexible composite fabric functionalized with SiO2 / ZnO / ZIF-8 core-shell nanoparticles.
[0051] The SiO2 / ZnO / ZIF-8 core-shell nanoparticles used can be obtained by the following specific preparation process: weigh 20mmol zinc acetate dihydrate and 6mmol ascorbic acid, dissolve them in 100mL deionized water, and after they are completely dissolved, add 0.9613g SiO2 nanospheres, stir for 10min, and ultrasonicate for 15min to obtain a dispersed solution; weigh 40mmol hexamethylenetetramine and add it to the dispersed solution, stir for 3min, and ultrasonicate for 5min; then transfer it to a water bath and react at 90℃-100℃ for 2-4h; after the reaction is completed, obtain the reaction product by centrifugation, repeatedly wash it with deionized water and ethanol for 3 to 5 times, and dry it at 60℃ for 12 hours to obtain a yellow powder; grind the yellow powder and transfer it to a muffle furnace, calcine it in an air atmosphere, and the heating rate is 5℃-10℃ / min, calcine it at 600℃-800℃ for 1-3h to obtain a white powder, and grind it to obtain SiO2 / ZnO core-shell nanoparticles; take 0.2g SiO2 / ZnO core-shell nanoparticles were dissolved in 25mL DMF and ultrasonicated for 15min, then 0.2932g 2-methylimidazole was added and ultrasonicated for 5min. After the ultrasonication, the dispersion was transferred to an oil bath and reacted at 90℃-110℃ for 1-3h. After the reaction, the reaction product was obtained by centrifugation, washed repeatedly with ethanol for 3 to 5 times, and dried at 60℃ for 12h to obtain the desired product, which is SiO2 / ZnO / ZIF-8 core-shell nanoparticles.
[0052] Example 2
[0053] 1.6848g P(VDF-HFP) was weighed and dissolved in a mixed solvent of 4mL acetone and 6mL DMF, and stirred at 40°C for 2h to obtain a polymer solution with a mass concentration of 16wt%, and three portions of the polymer solution were prepared in total; 0.8420g SiO2 / Zn2SiO4 core-shell nanoparticles were added to one of the polymer solutions and stirred for 4h to obtain a composite solution; the electrospinning machine parameters were set as spinning voltage of 12kV, propulsion rate of 0.9mL / h, and receiving distance of 16cm; the polymer solution, composite solution, and polymer solution were successively transferred to the electrospinning machine for continuous electrospinning for 3h, 6h, and 3h, respectively; after spinning, the composite fiber membrane was transferred to an oven and dried at 60°C for 8h to obtain a flexible composite fabric functionalized with SiO2 / Zn2SiO4 core-shell nanoparticles.
[0054] The SiO2 / Zn2SiO4 core-shell nanoparticles used are prepared by the following specific preparation process: 20mmol zinc nitrate hexahydrate and 6mmol ascorbic acid are weighed, dissolved in 100mL deionized water, and after complete dissolution, 0.9613g SiO2 nanospheres are added, stirred for 10min, and ultrasonicated for 15min to obtain a dispersed solution; 40mmol hexamethylenetetramine is weighed and added to the dispersed solution, stirred for 3min, and ultrasonicated for 5min; then transferred to a water bath and reacted at 90℃-100℃ for 2-4h; after the reaction is completed, the reaction product is obtained by centrifugation, repeatedly washed with deionized water and ethanol for 3 to 5 times, and dried at 60℃ for 12 hours to obtain a yellow powder; the yellow powder is ground and transferred to a muffle furnace, calcined in an air atmosphere, the heating rate is 5-10℃ / min, and calcined at 900℃-1100℃ for 2-4h to obtain a white powder, and the desired product is obtained after grinding, which is SiO2 / Zn2SiO4 core-shell nanoparticles.
[0055] Example 3
[0056] Weigh 1.6548g P(VDF-HFP) and dissolve it in a mixed solvent of 5mL acetone and 5mL DMF, stir at 40℃ for 2h to obtain a polymer solution with a mass concentration of 16wt%; take 0.8270g SiO2 / ZnO core-shell nanoparticles and add them to the polymer solution, stir for 4h to obtain a composite solution; set the electrospinning machine parameters as spinning voltage of 9.5kV, propulsion rate of 0.8mL / h, and receiving distance of 14.5cm; successively transfer the polymer solution, composite solution, and polymer solution to the electrospinning machine for continuous electrospinning for 3h, 6h, and 3h, respectively; after spinning, transfer the composite fiber membrane to an oven and dry it at 60℃ for 8h to obtain a flexible composite fabric functionalized with SiO2 / ZnO core-shell nanoparticles.
[0057] The SiO2 / ZnO core-shell nanoparticles used were prepared using the following specific preparation process: 20 mmol zinc acetate dihydrate and 6 mmol ascorbic acid were weighed, dissolved in 100 mL deionized water, and after complete dissolution, 0.9613 g SiO2 nanospheres were added, stirred for 10 min, and ultrasonicated for 15 min to obtain a dispersed solution; 40 mmol hexamethylenetetramine was weighed and added to the dispersed solution, stirred for 3 min, and ultrasonicated for 5 min; then the solution was transferred to a water bath and reacted at 90°C-100°C for 2-4 h; after the reaction, the reaction product was obtained by centrifugation, repeatedly washed with deionized water and ethanol for 3 to 5 times, and dried at 60°C for 12 hours to obtain a yellow powder; the yellow powder was ground and transferred to a muffle furnace, calcined in an air atmosphere at a heating rate of 5°C-10°C / min, and calcined at 600°C-800°C for 2-4 h to obtain a white powder, which was ground to obtain the desired product, namely SiO2 / ZnO core-shell nanoparticles.
[0058] Example 4
[0059] In this embodiment, the mass concentration of the polymer solution is 13%, and the volume ratio of acetone and DMF in the polymer solution is 6:4 to form a mixed solvent. During the electrospinning process, the spinning voltage is 8KV, the propulsion rate is 1.0mL / h, and the receiving distance is 14cm. Others are the same as in Example 1.
[0060] Example 5
[0061] In this embodiment, in the composite solution, the nanoparticles account for 40 wt% of the polymer mass. The spinning voltage during the electrospinning process is 12 KV, the propulsion rate is 1.0 mL / h, and the receiving distance is 18 cm. Others are the same as in embodiment 1.
[0062] Example 6
[0063] In this embodiment, in the composite solution, the nanoparticles account for 60 wt % of the polymer mass, and the rest is the same as in Embodiment 3.
[0064] Performance Testing:
[0065] 1) SEM test: The samples prepared in the above embodiments were observed under a scanning electron microscope. Figure 1The microscopic morphology of the SiO2 / ZnO / ZIF-8 core-shell nanoparticle sample prepared in Example 1 is formed by in-situ chemical assembly of SiO2 nanospheres, nano ZnO particles and bulk nano ZIF-8 particles, wherein the nano ZnO particles are evenly dispersed on the surface of the SiO2 nanospheres, and the bulk ZIF-8 particles are further wrapped on the surface, presenting an overall polyhedron-coated spherical morphology, with an overall particle size of 600-900nm, and the ZIF-8 blocks distributed on the surface are 90-110nm; the particle size of the fine ZnO nanoparticles coated on the surface of the SiO2 nanospheres is 10-30nm. Figure 2 The microscopic morphology of the SiO2 / Zn2SiO4 core-shell nanoparticle sample obtained in Example 2 is formed by the surface solid phase reaction between the SiO2 nanospheres and the surface nano ZnO particles. Therefore, the sample presents a smooth spherical morphology with obvious grooves on the surface. The overall particle size is 540-600nm. Figure 3 The microscopic morphology of the SiO2 / ZnO core-shell nanoparticle sample obtained in Example 3 is a spherical morphology covered with dense fine particles. The core-shell structure is composed of fine nano ZnO particles wrapped on the surface of SiO2 nanospheres. The overall particle size is 500-700nm; the particle size of the fine ZnO nanoparticles distributed on the surface is about 10-30nm. Figure 4 The structural schematic diagram of the composite flexible fabric obtained in Example 1 and the morphology and cross-sectional diagram of each layer are shown, wherein the upper and lower layers are polymer electrospun fiber layers, and the middle layer is a functional electrospun fiber layer modified with nanoparticles; it can be seen from the figure that the polymer fibers in each layer are uniform in size and interwoven into a three-dimensional mesh porous structure. In the functional electrospun fiber layer, it can be observed that the nanoparticles are uniformly dispersed in the mesh structure interwoven with the polymer fibers and embedded on the fiber surface. The nanoparticles have a particle size of 500-900nm overall. The polymer fiber diameters of the upper and lower polymer electrospun fiber layers are between 100 and 700nm; the polymer fiber diameter of the middle functional electrospun fiber layer is between 200 and 1000nm. It can be seen from the figure that the total thickness of the three layers of the composite flexible fabric obtained in Example 1 is about 250цm. The thickness of each layer and the total thickness can be adjusted according to the needs of the fabric by adjusting the electrospinning time, and can meet the multifunctional requirements of the composite flexible fabric of the present invention between a few microns and millimeters.
[0066] 2) Test of reflectivity in the ultraviolet-visible-near infrared band and emissivity in the infrared band: The composite flexible fabrics prepared in the above embodiments were subjected to radiative cooling performance tests, and their reflectivity in the ultraviolet-visible-near infrared band and emissivity in the infrared band were tested. The test results show that the average reflectivity in the ultraviolet-visible-near infrared band of the composite flexible fabrics prepared in the embodiments is above 84%, and the emissivity in the infrared atmospheric window band within the range of 8-13 μm is close to 95%. Figure 5, is the spectrum test result of the composite flexible fabric prepared in Example 1 for reflectivity in the ultraviolet-visible-near infrared band and emissivity in the infrared band. Figure 5 It can be seen that the flexible composite fabric prepared in Example 1 has a high reflectivity in the ultraviolet-visible-near infrared band, and its average reflectivity can reach 84.7%, which can reflect most of the incident solar radiation. The flexible composite fabric prepared in Example 1 has a very strong emissivity in the infrared atmospheric window band (8-13 μm), and its average emissivity is 94.9%, which can carry out strong heat exchange with the low-temperature universe through the atmospheric window.
[0067] 3) Outdoor cooling effect test: The composite flexible fabrics prepared in each embodiment were tested for outdoor cooling effect. The test results of embodiment 1 are as follows: Figure 6 As shown (the curve corresponding to "the fabric" in the figure is the test curve of the composite flexible fabric prepared in Example 1), compared with the purchased pure cotton fabric, it can achieve a stable cooling effect, with a maximum cooling range of 2.9° C. The test results of other embodiments are comparable to those of Example 1.
[0068] 4) Energy collection performance: The energy collection performance of the composite flexible fabrics prepared in the above embodiments was evaluated by friction nanogenerator performance test. The composite flexible fabrics prepared in each embodiment were used as negative electrode materials and combined with nylon film to test the energy collection index of the flexible fabric friction nanogenerator. The test results of each embodiment showed that they all had excellent energy collection performance. Figure 7-9 is the test result of Example 1, Figure 7 As shown in the figure, at different operating frequencies (2Hz-6Hz), the open circuit voltage of the device can reach ~48.99V. Figure 8 As shown in the figure, when the external load is 60MΩ, the maximum output power of the device can reach 9.87μW (10.97mW·m -2 ). Fig. 9 As shown, after 9600 cycles of continuous operation, the device still maintains good stability.
[0069] 5) Hydrophobicity test: The composite flexible fabric prepared in Example 1 was subjected to a hydrophobicity test, and the water contact angle test diagram thereof is shown in the attached figure. Fig.10 As shown in the figure, the contact angle is 134.3°, which has good hydrophobicity. The fabrics made in other embodiments also have comparable hydrophobicity.
[0070] 6) Co-culture antibacterial test: The composite flexible fabrics prepared in each embodiment were co-cultured with Escherichia coli and Staphylococcus aureus, and their colony patterns were observed to test their antibacterial properties. Fig.11The test results of the flexible fabric of Example 1 are shown. Compared with the blank control group, the antibacterial rates of the composite flexible fabric of Example 1 against Escherichia coli and Staphylococcus aureus are both greater than 99.9%, showing high-efficiency and broad-spectrum antibacterial activity.
Claims
1. A multifunctional composite flexible fabric, characterized in that: The composite flexible fabric has multiple functions of radiation cooling, energy collection, hydrophobicity and antibacterial; The composite flexible fabric is composed of a plurality of electrospun fiber layers, each layer being formed by electrospinning in an upper and lower order; including at least two layers of polymer electrospun fiber layers and at least one layer of nano-functional electrospun fiber layer, wherein the nano-functional electrospun fiber layer is an intermediate layer, forming a sandwich structure with the polymer electrospun fiber layers located on the upper and lower surfaces respectively; The polymer electrospun fiber layer is formed by a plurality of polymer fibers, namely, first polymer fibers, crossing to form a three-dimensional mesh porous structure; The nano-functional electrospun fiber layer comprises a plurality of polymer fibers, namely, second polymer fibers, and a plurality of nanoparticles, wherein the second polymer fibers are crossed to form a three-dimensional mesh porous structure, and the nanoparticles are evenly distributed in or on the mesh porous structure formed by the second polymer fibers and embedded on the second polymer fibers; The material of the polymer fiber is selected from one or more of polyvinylidene fluoride and its series copolymers; the nanoparticles are at least one of SiO2 / ZnO core-shell particles, SiO2 / Zn2SiO4 core-shell particles or SiO2 / ZnO / ZIF-8 core-shell particles.
2. The multifunctional composite flexible fabric according to claim 1, characterized in that: The material of the polymer fiber is selected from one or more of PVDF, PVDF-HFP and PVDF-TRFE.
3. The multifunctional composite flexible fabric according to claim 1, characterized in that: The composite flexible fabric consists of three layers, two single-layer polymer electrospun fiber layers and one single-layer nano-functional electrospun fiber layer, which are, in top-bottom order, the first polymer electrospun fiber layer, the nano-functional electrospun fiber layer, and the second polymer electrospun fiber layer.
4. The multifunctional composite flexible fabric according to claim 3, characterized in that: The diameter of the first polymer fiber is 100-700 nm; the diameter of the second polymer fiber is 200-1000 nm.
5. The multifunctional composite flexible fabric according to claim 3, characterized in that: The content of the nanoparticles is 40-60% of the mass fraction of the second polymer fiber.
6. The multifunctional composite flexible fabric according to claim 1, characterized in that: Furthermore, the SiO2 / ZnO core-shell particles are formed by a core-shell structure of fine nano-ZnO particles wrapped on the surface of SiO2 nanospheres; the SiO2 / ZnO / ZIF-8 core-shell particles are formed by in-situ chemical assembly of SiO2 nanospheres, nano-ZnO particles and bulk nano-ZIF-8 particles, wherein the nano-ZnO particles are uniformly dispersed on the surface of the SiO2 nanospheres, and the bulk ZIF-8 particles are further wrapped on the surface; the SiO2 / Zn2SiO4 core-shell particles are formed by a surface solid-phase reaction of SiO2 nanospheres and nano-ZnO particles on the surface to form a core-shell structure; wherein the diameter of the SiO2 nanospheres is 500-600nm, the diameter of the nano-ZnO particles is 10-30nm, and the size of the bulk nano-ZIF-8 particles is 90-110nm.
7. The multifunctional composite flexible fabric according to claim 1, characterized in that: The radiation cooling function means that: the solar reflectivity of the composite flexible fabric reaches more than 84.7%; the infrared emissivity of the composite flexible fabric in the infrared atmospheric window band of 8-13 μm reaches more than 94.9%; The energy collection function refers to: the energy collection index of the composite flexible fabric friction nanogenerator is that the open circuit voltage reaches 48.99V at an operating frequency of 2Hz-6Hz; the maximum output power reaches 10.97mW·m when the external load is 60MΩ -2 The hydrophobic property of the composite flexible fabric shows that the water contact angle reaches 134.3°; the antibacterial function of the composite flexible fabric includes that the antibacterial rates of Escherichia coli and Staphylococcus aureus are both greater than 99.9%.
8. A method for preparing the multifunctional composite flexible fabric according to any one of claims 1 to 7, characterized in that: Includes steps: 1) dissolving a polymer material in a mixed solvent to form a precursor solution; 2) adding the functional nanoparticle material to the precursor solution to obtain a composite solution; 3) The precursor solution, the composite solution and the precursor solution are sequentially subjected to continuous electrospinning, and the multifunctional composite flexible fabric is obtained after drying. Wherein, the polymer material in step 1) is selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene or polyvinylidene fluoride-trifluoroethylene; the mixed solvent contains a high boiling point solvent and a low boiling point solvent, the high boiling point solvent is one of N,N-dimethylformamide DMF or N,N-dimethylacetamide DMAC; the low boiling point solvent is acetone; The functional nanoparticle material described in step 2) is selected from SiO2 / ZnO core-shell particles, SiO2 / Zn2SiO4 core-shell particles or SiO2 / ZnO / ZIF-8 core-shell particles.
9. The method for preparing the multifunctional composite flexible fabric according to claim 8, characterized in that: The volume ratio of the high boiling point solvent to the low boiling point solvent is 6:4 to 4:6; the mass fraction of the polymer material in the precursor solution is 13 to 16 wt %; in step 2), the functional nanoparticle material accounts for 40 to 60% of the mass fraction of the polymer material in the composite solution.
10. The method for preparing the multifunctional composite flexible fabric according to claim 8, characterized in that: In the electrospinning process described in step 3), the spinning voltage is 8 to 12 kV, the propulsion speed is 0.8 to 1.0 mL / h, and the receiving distance is 14 to 18 cm.
11. The method for preparing the multifunctional composite flexible fabric according to claim 8, characterized in that: The specific preparation method of the functional nanoparticle material in step 2) is: a) adding SiO2 particles, an inorganic zinc source and ascorbic acid into an aqueous solution, and subjecting the aqueous solution to ultrasonic treatment to obtain a SiO2 dispersion; The inorganic zinc source is one of zinc acetate and zinc nitrate; b) adding hexamethylenetetramine HMTA to the SiO2 dispersion, stirring and then ultrasonically treating to obtain a first pre-solution; The molar ratio of SiO2:inorganic zinc source:ascorbic acid:hexamethylenetetramine is 8:10:3:20; c) subjecting the first pre-solution to a solution reaction at a temperature of 90 to 100° C. for 2 to 4 hours to obtain a precipitated product; d) centrifugally separating the precipitated product, washing and drying the precipitated product to obtain a powder; grinding the powder, calcining in an air atmosphere at a heating rate of 5 to 10° C. / min and a holding time of 1 to 3 hours to obtain the SiO2 / ZnO core-shell particles at a temperature of 600 to 800° C., or obtaining the SiO2 / Zn2SiO4 core-shell particles at a temperature of 900 to 1100° C.; e) mixing the SiO2 / ZnO core-shell particles, N,N-dimethylformamide (DMF) and 2-methylimidazole, and subjecting the mixture to ultrasonic treatment to obtain a second pre-solution; f) subjecting the second pre-solution to a solution reaction at a temperature of 90 to 110° C. for 1 to 3 hours to obtain a precipitated product; The precipitated product is centrifuged, washed, and dried to obtain the SiO2 / ZnO / ZIF-8 core-shell particles.
Citation Information
Patent Citations
Method for preparing polyvinylidene fluoride and titanium dioxide (PVDF / TiO2) compounded nanofiber membrane
CN102704190A
SiO2 / PVDF-HFP composite fiber membrane and preparation method and application thereof
CN110518177A
Preparation method of clothing nonwoven material with high radiation refrigeration effect
CN110920191A
Method for preparing underwear with antibacterial effect by utilizing electrostatic spinning method
CN111251693A
Preparation method for cellulose nano fiber composite film for treating printing and dyeing wastewater
CN111379074A
Cited By
Composite nanofiber membrane sound absorption material and preparation method thereof
CN120061054A